ANTAGONISTIC ACTIVITY AND PLANT GROWTH PROMOTING RHIZOBACTERIA ISOLATED FROM FOREST PLANT RHIZOSPHERE AGAINST FUSARIUM SOLANI ON THUJA SEEDLINGS - Yasin, B.; Ali, O. Omer; Rashid, T. Sulaiman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Root diseases are one of the main forest nursery problems that have a significant impact on forest production which are caused by Fusarium solani. Rhizobacteria from healthy forest soils were isolated and screened in streak method to select antagonistic strains against F. solani. Two isolates showed high antagonistic activity and molecularly identified as Paenibacillus sp. and Pseudomonas sp. The capability of the Paenibacillus sp. and Pseudomonas sp. were tested in greenhouse plastic containers experiments against F. solani. Soil bacterization with Paenibacillus sp. and Pseudomonas sp. significantly protected thuja seedlings from F. solani compared to the untreated control seedlings. The containers added by Paenibacillus sp. and pseudomonas sp. are also showed plant growth promotion including shoot length, root length, dry and wet weights of the seedlings as well as the chlorophyll contents of the thuja seedlings compared to the untreated control plants. In this research it has been showing that the rhizobacterial treatments have potential to decrease the effect of fungal disease severity, promoting the plant growth and also helps plants to maintain a good health.